Skip to main content

Section 5.3 Properties of Roots

In this section, we fill in the missing details when deriving the properties of the roots of a simple Lie algebra \(\gg\text{.}\)

We assume that a Cartan algebra \(\hh\subset\gg\) of simultaneously diagonalizable elements has been chosen, and that \(\gg\) has been decomposed into eigenspaces

\begin{equation} \gg = \hh \mathop{\oplus}_{\alpha\in R} \gg_\alpha ,\tag{5.3.1} \end{equation}

so that, for any \(H\in\hh\text{,}\) we have

\begin{equation} [H,X_\alpha] = \alpha(H) X_\alpha\tag{5.3.2} \end{equation}

for a finite set of roots \(R\subset\hh^*\text{.}\) The Jordan–Chevalley decomposition shows that any linear operator can be divided uniquely into the sum of a diagonalizable operator and a nilpotent operator. Thus, nonzero elements of \(\hh\) can not be nilpotent.

Since \(\gg\) is simple, the Killing form \(B\) on \(\gg\) is nondegenerate. We claimed in the previous section that

\begin{equation} B(\gg_\alpha,\gg_\beta) = 0 = B(\gg_\alpha,\hh)\tag{5.3.3} \end{equation}

for \(\alpha+\beta\ne0\) (and \(\alpha\ne0\text{,}\) since \(0\not\in R\)).

To verify these claims, we need the identity (3.6.6), which was derived in Section 3.6 using components. An alternative derivation uses the following simple lemma about traces. Since

\begin{equation} \tr(XY) = \tr(YX) ,\tag{5.3.4} \end{equation}

the trace is cyclic, so that, for instance,

\begin{equation} \tr(XYZ) = \tr(ZXY) .\tag{5.3.5} \end{equation}

Thus,

\begin{equation} \tr([X,Y]Z) = \tr(XYZ-YXZ) = \tr(XYZ-XZY) = \tr(X[Y,Z])\tag{5.3.6} \end{equation}

which implies that

\begin{equation} B([X,Y],Z) = B(X,[Y,Z]) .\tag{5.3.7} \end{equation}

It is now straightforward to compute for any \(X\in\gg_\alpha\text{,}\) \(Y\in\gg_\beta\) (where we treat \(\gg_0\) as \(\hh\)) and \(H\in\hh\) that

\begin{equation} 0 = -B([X,H],Y) + B(X,[H,Y]) = \bigl(\alpha(H)+\beta(H)\bigr) B(X,Y)\tag{5.3.8} \end{equation}

so that \(B(X,Y)=0\) unless \(\alpha+\beta=0\in\hh^*\text{,}\) as claimed.

Subsection 5.3.1 Preferred Cartan Elements

Since \(B\) is nondegenerate, for any \(X_\alpha\in\gg_\alpha\text{,}\) there must be some \(Y_\alpha\in\gg\) such that

\begin{equation} B(X_\alpha,Y_\alpha) \ne 0 ,\tag{5.3.9} \end{equation}

and (5.3.3) now implies that \(Y_\alpha\in\gg_{-\alpha}\text{.}\) Thus, if \(\alpha\) is a root, so is \(-\alpha\text{,}\) and we have

\begin{equation} [H,Y_\alpha] = -\alpha(H) Y_\alpha .\tag{5.3.10} \end{equation}

Furthermore, since \(\alpha\ne0\text{,}\) there must be some \(H\in\hh\) such that \(\alpha(H)\ne0\text{.}\) Using (5.3.7) now leads to

\begin{align} B([X_\alpha,Y_\alpha],H) \amp= B(X_\alpha,[Y_\alpha,H]) = B(X_\alpha,\alpha(H)Y)\notag\\ \amp= \alpha(H) B(X_\alpha,Y_\alpha) \ne 0\tag{5.3.11} \end{align}

which implies that

\begin{equation} 2 H_\alpha = [X_\alpha,Y_\alpha] \ne 0\tag{5.3.12} \end{equation}

where the first equality is a definition.

We now claim that \(\alpha(H_\alpha)\ne0\text{.}\) If instead \(\alpha(H_\alpha)=0\text{,}\) then (5.3.2) and (5.3.10) imply that

\begin{equation} [H_\alpha,X_\alpha] = 0 = [H_\alpha,Y_\alpha] ,\tag{5.3.13} \end{equation}

so both \(X_\alpha\) and \(Y_\alpha\) commute with \(H_\alpha\text{.}\) Consider now any representation \(V\) of \(\gg\text{,}\) and suppose that the image of \(H_\alpha\text{,}\) which we will also call \(H_\alpha\text{,}\) has an eigenspace

\begin{equation} V_\lambda = \{v\in V: H_\alpha v = \lambda v\}\tag{5.3.14} \end{equation}

for some fixed eigenvalue \(\lambda\text{.}\) Since \(X_\alpha\) and \(Y_\alpha\) commute with \(H_\alpha\text{,}\) they each take eigenvectors to eigenvectors, that is, they take \(V_\lambda\) to itself. So \(V_\lambda\) is itself a representation of the subalgebra generated by \(\{H_\alpha,X_\alpha,Y_\alpha\}\text{.}\) Thus, as matrices acting on \(V_\lambda\text{,}\) we must have

\begin{equation} [X_\alpha,Y_\alpha] = 2 H_\alpha = 2 \lambda\tag{5.3.15} \end{equation}

since representations preserve commutators (by definition), and \(H_\alpha\) is a multiple of the identity matrix when acting on \(V\text{.}\) Taking the trace of both sides immediately forces \(\lambda=0\text{.}\)  1  Thus, the only eigenvalue of \(H_\alpha\) is \(0\text{,}\) which means that \(\beta(H_\alpha)=0\) for any root \(\beta\text{,}\) which in turn forces \(H_\alpha=0\text{.}\) This contradiction establishes the claim, namely that \(\alpha(H_\alpha)\ne0\text{.}\)

We can now rescale \(X_\alpha\) and \(Y_\alpha\) if necessary to obtain

\begin{equation} \alpha(H_\alpha) = 1 ,\tag{5.3.16} \end{equation}

thus demonstrating that the subalgebra generated by \(\{H_\alpha,X_\alpha,Y_\alpha\}\) is a copy of \(\sl(2,\RR)\text{.}\) Although this construction does not determine \(X_\alpha\) and \(Y_\alpha\) uniquely, \(H_\alpha\) is uniquely determined. These special elements of \(\hh\) will be referred to as preferred Cartan elements.

Subsection 5.3.2 Root Angles

As discussed in the previous section, \(\{H_\alpha,X_\alpha,Y_\alpha\}\) form a standard basis for \(\sl(2,\RR)\text{,}\) the split real form of \(\su(2)\text{.}\) Thus, all representations of this Lie subalgebra of \(\gg\) have half-integer eigenvalues, and in particular, \(\beta(H_\alpha)\in\frac12\ZZ\) for all roots \(\beta\text{.}\) The restriction of \(\gg\) to real linear combinations of \(H_\alpha\text{,}\) \(X_\alpha\text{,}\) \(Y_\alpha\) for all \(\alpha\in R\) is therefore a real subalgebra of \(\gg\text{,}\) and is in fact the split real form of \(\gg\text{.}\)

As before, choose \(T_\alpha\in\hh\) to be the element determined by

\begin{equation} \alpha(H) = B(T_\alpha,H)\tag{5.3.17} \end{equation}

for all \(H\in\hh\text{.}\) We need to verify that \(T_\alpha\) is a multiple of \(H_\alpha\text{.}\)

Using (5.3.11) and (5.3.12) we have

\begin{equation} B(2H_\alpha,H) = \alpha(H) B(X_\alpha,Y_\alpha)\tag{5.3.18} \end{equation}

so that in particular

\begin{equation} B(2H_\alpha,H_\alpha) = \alpha(H_\alpha) B(X_\alpha,Y_\alpha) = B(X_\alpha,Y_\alpha)\tag{5.3.19} \end{equation}

which is furthermore nonzero by assumption. Thus,

\begin{equation} B(2H_\alpha,H) = B(T_\alpha,H) B(2H_\alpha,H_\alpha) = B\bigl(B(2H_\alpha,H_\alpha)T_\alpha,H\bigr)\tag{5.3.20} \end{equation}

for all \(H\in\hh\text{,}\) and we conclude that

\begin{equation} T_\alpha = \frac{H_\alpha}{B(H_\alpha,H_\alpha)} .\tag{5.3.21} \end{equation}

as claimed previously. It now follows immediately that

\begin{equation} \frac{B(H_\alpha,H_\beta)}{B(H_\alpha,H_\alpha)} = B(T_\alpha,H_\beta) = \alpha(H_\beta) \in\frac12\ZZ\tag{5.3.22} \end{equation}

leading to the angles and ratios discussed in Section 5.2.

Subsection 5.3.3 Multiples of Roots, and Multiplicity

It remains to show that the only multiples of a root \(\alpha\) that are roots are \(\pm\alpha\text{,}\) and that each root only occurs once, that is, that \(|\gg_\alpha|=1\text{.}\)

We have shown that \(\{H_\alpha,X_\alpha,Y_\alpha\}\) is a standard basis for \(\sl(2,\RR)\text{,}\) so that \(X_\alpha\text{,}\) \(Y_\alpha\) act as raising and lowering operators, respectively, for \(H_\alpha\text{.}\) Suppose that \(Z\in\gg_\alpha\text{,}\) so that

\begin{equation} [H_\alpha,Z] = \alpha(H_\alpha) Z = Z .\tag{5.3.23} \end{equation}

We know that all representations of \(\sl(2,\RR)\) consist of integer or half-integer “ladders”. So how does \(\sl(2,\RR)\) act on \(Z\text{?}\) Moving down the ladder,

\begin{equation} Z_0 = [Y_\alpha,Z]\tag{5.3.24} \end{equation}

is an element of \(\hh\text{,}\) since \(Y_\alpha\) decreases all the eigenvalues of \(Z\) by \(\alpha\text{,}\) that is

\begin{align} [H,Z_0] \amp= \bigl[H,[Y_\alpha,Z]\bigr] = \bigl[[H,Y_\alpha],Z\bigr] + \bigl[Y_\alpha,[H,Z]\bigr]\notag\\ \amp= (-\alpha+\alpha) [Y_\alpha,Z] = 0\tag{5.3.25} \end{align}

for any \(H\in\hh\text{.}\) Since \(B\) is positive-definite on \(\hh\text{,}\) we can expand \(Z_0\) as

\begin{equation} Z_0 = z H_\alpha + H_\perp\tag{5.3.26} \end{equation}

where

\begin{equation} B(H_\alpha,H_\perp) = 0 .\tag{5.3.27} \end{equation}

But

\begin{equation} B(H_\alpha,H_\perp) = 0 \Longrightarrow B(T_\alpha,H_\perp) = 0 \Longrightarrow \alpha(H_\perp) = 0\tag{5.3.28} \end{equation}

so that

\begin{equation} \alpha(Z_0) = z\alpha(H_\alpha)+0 = z.\tag{5.3.29} \end{equation}

Putting this all together, we have

\begin{equation} [X_\alpha,Z_0] = -[Z_0,X_\alpha] = -\alpha(Z_0) X_\alpha = -z X_\alpha .\tag{5.3.30} \end{equation}

But moving back up the ladder has to yield a multiple of \(Z\text{,}\) and we conclude that \(Z\) is itself a multiple of \(X_\alpha\text{,}\) thus confirming that \(|\gg_\alpha|=1\) (and also that \(|\hh_\alpha|=1\)).

The argument against any other multiples of \(\alpha\) other than \(\pm\alpha\) being roots is similar. If \(c\alpha\) is a root, then choosing \(Z\in\gg_{c\alpha}\) leads to

\begin{equation} [H_\alpha,Z] = (c\alpha)(H_\alpha) Z = c Z\tag{5.3.31} \end{equation}

which forces \(c\) to be half-integer. Suppose \(c\in\ZZ\text{.}\) Then we can move up or down the ladder from \(Z\) to some element \(Z_1\in\gg_\alpha\text{.}\) By the argument above, \(Z_1\) must be a multiple of \(X_\alpha\text{.}\) But then the ladder collapses, and \(c=\pm1\text{.}\) In particular, \(2\alpha\) can not be a root. But now \(\frac12\alpha\) also can not be a root, which rules out half-integer values of \(c\text{.}\)

Remark 5.3.1. Alternate proof that each root occurs only once, without multiples.

The one-dimensional nature of the root spaces can also be established by first showing that the corresponding piece of the Cartan algebra is one-dimensional, then using the properties of \(\sl(2,\RR)\) to argue that there are no non-unit multiples of roots. This proof does not use the positive-definite nature of the Killing form on \(\hh\text{.}\)

Let \(\{e_m\}\) be a basis for \(\hh\) and set \(\lambda=\alpha(e_m)\text{.}\) Then for any \(H\in\hh\) we have \(H=h^m e_m\) so that \(\alpha(H)=h^m\lambda_m\text{.}\) Since \(\alpha\ne0\text{,}\) we must have \(\lambda_k\ne0\) for some \(k\text{.}\) But then \(h^k\) can always be chosen so that \(\alpha(H)=0\text{.}\) Thus, \(\ker(\alpha)\) must be \((n-1)\)-dimensional. (It can't be \(n\)-dimensional since \(\alpha\ne0\text{.}\))

Now choose \(H\in\ker(\alpha)\) and \(K\in\hh_\alpha:=[\gg_\alpha,\gg_{-\alpha}]\text{.}\) Then \(\alpha(H)=0\) and \(K=[X,Y]\) with \(X\in\gg_\alpha\) and \(Y\in\gg_{-\alpha}\text{.}\) We compute

\begin{equation} B(H,K) = B(H,[X,Y]) = B([H,X],Y) = \alpha(H) B(X,Y) = 0\tag{5.3.32} \end{equation}

which implies that \(H\in\hh_\alpha^\perp\) (in \(\hh\)). Since \(\hh_\alpha^\perp\) can not be all of \(\hh\) by the nondegeneracy of the Killing form \(B\text{,}\) we have shown that \(\hh_\alpha^\perp=\ker(\alpha)\text{.}\)

Thus, \(\hh_\alpha^\perp\) is \((n-1)\)-dimensional, which means that \(\hh_\alpha\) must be 1-dimensional.

We constructed a nonzero element \(H_\alpha\in\hh_\alpha\) in (5.3.12), and showed further that \(\alpha(H_\alpha)\ne0\text{.}\) We conclude that \(\hh_\alpha=\langle H_\alpha\rangle\text{.}\)

Since \(\hh_\alpha\) is one-dimensional, and \(\{H_\alpha,X_\alpha,Y_\alpha\}\) is a standard basis for \(\sl(3,\RR)\text{,}\) \(\hh_\alpha\oplus\gg_\alpha\oplus\gg_{-\alpha}\) must be the adjoint representation of \(\sl(3,\RR)\text{.}\) Thus, \(|\gg_{\pm\alpha}|=1\text{,}\) and no other multiples of \(\alpha\) can be roots.

(5.3.15) always forces the trace of \(H_\alpha\) to be zero, which forces the sum of the eigenvalues of \(H_\alpha\) to be zero. In the case considered here, however, there is only one eigenvalue, whose “sum” must still be zero.